2020
DOI: 10.3390/en13246695
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Heat Pump in a Ventilation Unit as an Economical and Ecological Source of Heat for the Ventilation System of an Indoor Swimming Pool Facility

Abstract: Air handling units are usually used to maintain the thermal and humidity parameters in indoor swimming pools that are used for lap swimming and recreation. Their use throughout the year consumes much more energy than, for example, air conditioning in residential or office buildings. Their considerable energy consumption is due to the need for their continuous operation to remove moisture gains from the evaporation of water and to heat the air and cover the heat losses of the pool. It is possible to design vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The calculations were carried out as described in Section 2.2 and took into account a variable ventilation air stream, as opposed to the standard procedures used to calculate the energy performance of a building [58][59][60]. Only those hours of the year were taken into account when the ground temperature was at least 2 K higher than the outside air temperature in winter, and only those summer hours when the outside air temperature was higher than 20 • C. These restrictions were introduced to make the calculated results more realistic, thus taking into account the fact that earth-to-air heat exchangers do not operate all year round.…”
Section: Full-year Heating and Cooling Gains And Energy Cost Of Harve...mentioning
confidence: 99%
“…The calculations were carried out as described in Section 2.2 and took into account a variable ventilation air stream, as opposed to the standard procedures used to calculate the energy performance of a building [58][59][60]. Only those hours of the year were taken into account when the ground temperature was at least 2 K higher than the outside air temperature in winter, and only those summer hours when the outside air temperature was higher than 20 • C. These restrictions were introduced to make the calculated results more realistic, thus taking into account the fact that earth-to-air heat exchangers do not operate all year round.…”
Section: Full-year Heating and Cooling Gains And Energy Cost Of Harve...mentioning
confidence: 99%
“…The swimming facility at Jøa is a state-of-the-art swimming facility which complies with the Norwegian passive house standard [22]. It includes a ventilation heat recovery system equipped with a heat pump, as recommended in the literature [5,43], and conventional water treatment, which research has found to be the most effective water treatment train [44].…”
Section: The Technical Systemsmentioning
confidence: 99%
“…Within the "renovation wave", the European Commission recommends paying particular attention to energy-reducing refurbishment in types of buildings that support education and public health, such as schools and hospitals [2]. In swimming facilities, which support education and public health, the potential for energy reduction is considerable [4] and the literature associates these facilities with high specific energy use [5] and a large dispersion in energy use. The specific energy use ranges from 400 kWh/(m 2 •a) to almost 1600 kWh/(m 2 •a) [6][7][8][9].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The need to reduce energy consumption contributes to the development of energyefficient and near-zero-energy buildings. Consequently, the overarching goal of HVAC systems is to provide the lowest possible energy consumption [1,2] for maintaining thermal comfort in a building [3]. Thermally activated ceilings can achieve high energy efficiency by reducing transmission losses and supply temperature during cooling.…”
Section: Introductionmentioning
confidence: 99%